2001
DOI: 10.1139/f01-093
|View full text |Cite
|
Sign up to set email alerts
|

Developing Baltic cod recruitment models. II. Incorporation of environmental variability and species interaction

Abstract: Abstract:We investigate whether a process-oriented approach based on the results of field, laboratory, and modelling studies can be used to develop a stock-environment-recruitment model for Central Baltic cod (Gadus morhua). Based on exploratory statistical analysis, significant variables influencing survival of early life stages and varying systematically among spawning sites were incorporated into stock-recruitment models, first for major cod spawning sites and then combined for the entire Central Baltic. Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
101
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 33 publications
(81 reference statements)
2
101
0
Order By: Relevance
“…Kö ster et al (2003) reported significant relationships between covariances of abundance estimates between early and late egg stages and between the late larval and the early juvenile stages but no significant relationship between year-class strength and larval abundance. These findings suggested that processes acting during the late larval and early juvenile phase were critical to year-class success, a finding recently shared by Baumann et al (2006).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Kö ster et al (2003) reported significant relationships between covariances of abundance estimates between early and late egg stages and between the late larval and the early juvenile stages but no significant relationship between year-class strength and larval abundance. These findings suggested that processes acting during the late larval and early juvenile phase were critical to year-class success, a finding recently shared by Baumann et al (2006).…”
Section: Discussionmentioning
confidence: 91%
“…Oxygen content and salinity have been shown to be the major environmental factors affecting the Baltic cod egg fertilization and survival rates (Wieland and Zuzarte 1991), and indirectly by determining the vertical overlap of cod eggs and their clupeid predators (Kö ster et al 2001). The principal mechanism influencing the replenishment of oxygen in the deep basins of the Baltic is the inflow of saline oxygen-rich waters from the North Sea.…”
mentioning
confidence: 99%
See 3 more Smart Citations